Radiation-induced leiomyosarcoma of the oropharynx - Maier Wolfgang; Ridder Gerd; Boedeker Carsten; Pfeiffer Jens; Kayser Gian (BMC, 2006)
Abstract Leiomyosarcoma is a malignant mesenchymal tumor originating from smooth muscle cells, which most frequently develops in the myometrium and in the gastro-intestinal tract. Reviewing the international literature, radiation-induced sarcoma arise in 0.035 to 0.2 % of all irradiated patients. Especially in the head and neck region, radiation-induced leiomyosarcoma is an extremely rare lesion. The authors report a case of a radiation-induced leiomyosarcoma of the tonsillar region of the oropharynx in a 51-year-old male patient, who had undergone radiation therapy of this region 38 years before. The lesion was treated by radical surgery. Diagnostic steps, histological presentation and therapy are described in detail and the literature concerning radiation induced malignancies in general as well as radiation induced leiomyosarcoma in particular is reviewed. The highlights of this case are an extremely uncommon location and a rare pathological entity of radiation induced malignancies.